Social infrastructure and centralisation in community response and recovery from disasters - Petr Matous; Scott Webster; Emma Pittaway; Jodie Bailie; Jo Longman; Nader Naderpajouh; Michele Barnes; Danielle Celermajer; David Schlosberg (Natural Hazards, 2026)
Response and recovery from climate-related disasters typically involve a mixture of formal and informal organising. There is an old and ongoing general debate about the efficiency and impact of formal versus informal organising, but evidence about the specific structures of these forms of response and recovery is lacking. In this study, we interviewed 68 informants from three different Australian communities impacted by floods and fires and conducted social network modelling to explore how formal and informal organising evolve, interact, complement and potentially come into tension with each other in response and recovery from compounding disasters. We explicitly measured and analysed the topology of community networks that are formed, mobilised and reshaped before and after disasters. Our focus is on how local community networks evolve in terms of centralisation—the extent to which a few key actors dominate coordination efforts—and reciprocity—the degree to which support and resources flow mutually between network members. The results across the three contexts provide empirical evidence on how centralisation combined with reciprocity can be mobilised during response and recovery to serve the communities and their resilience. The findings regarding the vital processes of shifting centralisation in disaster response and recovery can inform debates on frictions between formal and informal patterns of organising and illuminate how communities can most effectively respond to natural hazards within their local context.

Agency, social networks, and adaptation to environmental change - Michele L Barnes; Sarah Sutcliffe; Innocent Muly; Nyawira Muthiga; Stephen Wanyonyi; Petr Matous; Michael Murunga (Global Environmental Change, 2025)

An experiment in strengthening the networks of remote communities in the face of environmental change: leveraging spatially distributed environmental memory - Petr Matous; Yasuyuki Todo (Regional Environmental Change, 2018)